Why Should I Stay? Canadian Black Youth and Public Libraries - Matthews, Amber (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2025)
This study used narrative inquiry and critical approaches to race to explore Black youth perceptions of public libraries and community-based programs. The study was conducted in Ontario with youth aged 13 to 24 and parents of youth. Data was drawn from semi-structured interviews with youth and parents and an arts-based qualitative tool. Libraries were identified as safe and welcoming community spaces. However, youth feel poorly represented and seek youth programs with a race-conscious and inclusive approach. Core recommendations include equitable approaches to representation, strengthening relationships with partner organizations, and addressing performative approaches to inclusion. « Pourquoi devrais-je rester? » Les jeunes canadiens noirs et les bibliothèques publiques Résumé Cette étude a employé l'enquête descriptive ainsi qu'une approche critique par rapport à l'ethnicité afin d'explorer les perceptions des bibliothèques publiques et des programmes communautaires qu'ont les jeunes noirs. L'étude a été faite en Ontario avec des jeunes âgés de 13 à 24 ans, ainsi qu'avec leurs parents. Les données ont été extraites d'entrevues semi-structurées avec les jeunes et leurs parents et d'un outil artistique de nature qualitative. Les bibliothèques ont été identifiées comme étant des espaces communautaires sécuritaires et accueillants. Toutefois, les jeunes se sentent peu représentés et recherchent des programmes pour les jeunes qui prennent en compte les différentes ethnicités et qui adoptent une approche inclusive.